A 2.4GHz Non-Contact Biosensor System for Continuous Monitoring of Vital-Signs - Lie, Donald; Ichapurapu, Ravi; Jain, Suyash; Lopez, Jerry; Banister, Ronald; Nguyen, Tam; Griswold, John (IntechOpen, 2011)
None